An Approach of Top-DOWN Electric Generation Knowledge Graph Construction. Issue 1 (February 2021) - Liang, Hao; Peng, Xiaojun; Zhao, Ningning; Duan, Liguo; Yu, Pengfei; Fu, Da
Abstract: Knowledge Graph technology is a key research area of artificial intelligence technology. It has an obviously advantage in semantic processing and content interconnection, and widely used to provide intelligent information services in the open domain such as Web intelligent, NLP, user profile, etc. With the exploration and attempt of Knowledge Graph in vertical fields, it is confirmed that it can accelerated the intelligence application in all the electric generation life cycle, such as operation optimization, technical overhaul, intelligent marketing, material procurement, equipment maintenance. A Top-Down construction method of electric generation Knowledge Graph is proposed under the Kraftwerk-Kennzeichen system (KKS) to integrate electric generation knowledge and the knowledge management formation.